Análise da viabilidade do uso de lente de Fresnel para decomposição térmica do carbonato de cálcio - Araújo, Bruna Sene Alves (2018)
Solar energy is an energy source that does not produce waste and its capture has been studied extensively, mainly for processes that need high temperatures. The consumption of lime (CaO) has increased in recent decades and, despite its numerous applications, its industrial process generates large environmental impacts, such as: CO2 production and high energy expenditure, resulting from the burning of fossil fuels or electricity. In this scenario, this work has as main objective the study of the viability of the lime production (CaO) from the decomposition of Calcium Carbonate (CaCO3), using as a thermal source the solar energy concentrated by Fresnel Lenses. Thus, two experimental apparatus were constructed with Fresnel Lenses of different areas (A): A = 0.09 m² and A = 1 m². The heating dynamics of Fresnel Lens was predicted numerically involving the fundamental equations of Transport Phenomena and dimensional grouping (GA.M-1): solar radiation (G), lens area (A) and mass (M), which ranged from 2500 to 671500 W.kg-1. Subsequently, the heating dynamics was verified experimentally, using A = 0,09m² and aluminum and copper test bodies, not reaching satisfactory temperatures for the CaCO3 decomposition tests. Thus, the Fresnel Lens apparatus of 1 m2 and experiments of 30 min of solar exposition were used to evaluate the decomposition of CaCO3. In addition, the best material for the calcination reactor was investigated, analyzing: porcelain, cast iron and silicon carbide. Fresnel Lens were provided with heating ramps between 14 and 24 ° C.min-1, with the highest equilibrium temperature being 244 °C for lens of A = 0.09 m². Temperatures between 600 °C and 800 °C were reached with lens of A = 1 m², which were necessary for the chemical reaction to occur. It was possible to record mass losses and calculate the conversion by stoichiometry of the thermal decomposition reaction, achieving conversions of up to 81.82% for the 4443.96 W.kg-1 dimensional grouping (GA.M-1). Thus, it is concluded that for the studied masses (Reactor + MCaCO3) the solar concentration by Fresnel lenses was sufficient to perform the thermal decomposition.